Adaptive Reuse of the Industrial Building: A case of Energy Museum in Sanatistanbul, Turkey - Najmaldin Hussein (Journal of Contemporary Urban Affairs, 2017)
Industrial buildings as an example of cultural heritage transform our cultural identity from the past to the present and even for the future. Unfortunately, there are lots of industrial building which lost its function by converting the place to live and identifiable place. This research will clarify the reasons for conserving of the industrial heritage and by classification of international charters which are dealing with industrial heritage will introduce conservation methods for adaptive reuse of industrial buildings. As a case study, the research will focus on Energy Museum in Istanbul. To assess the building based on reusing principals. The study concludes that the Energy Museum is one of the successful examples of reuse of the building. It also concludes that less intervention in reusing a building can save the identity of the building.